Architectural differences of lower limb muscle-tendon for monozygotic twins with different sport experiences - Ishikawa, M.; Danno, Y.; Sano, K.; Kunimasa, Y.; Komi, P. V. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to examine architectural differences of lower limb muscle-tendon for monozygotic twins with different sport experiences and for monozygotic twins with same sport experiences. 50 monozygotic twins (MZT) participated in this study, consisting of 16 MZT with different sport experiences, 34 MZT with same sport experiences. Musculoskeletal ultrasonography is applied to measure the muscle fascicle length of gastrocnemius medialis (GM) muscle as well as Achilles and patella tendon cross-sectional area (CSA) and length. Achilles tendon was separately measured from the AT insertion point on the calcaneus to the distal end of soleus muscle (ATSOL) and to the AT junction between medial and lateral gastrocnemii muscles (ATGML), respectively. The measured intraclass correlation coefficient (ICC) clearly showed poor concordances in the ATSOL length of MZT with different sport experiences (ICC of 0.74), and good concordance in the MG fascicle length of MZT with different sport experiences (ICC of 0.83). Other parameters in all intra-pears showed excellent concordances (ICC>0.9). Thus, different concordances of AT length between GM and SOL parts can indicate the different plasticity by the structural and functional mechanics and different concordances between groups indicate that ATSOL and GM fascicle length are affected not only by genetic factors but also by acquired environmental factors.